2003
DOI: 10.1016/s0006-3495(03)74750-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Mannitol Diffusion in Human Dura Mater

Abstract: An in vitro experimental study of the control of the human dura mater optical properties at administration of aqueous solutions of glucose and mannitol has been presented. The significant increase of the dura mater optical transmittance under action of immersion liquids has been demonstrated. Diffusion coefficients of glucose and mannitol in the human dura mater tissue at 20 degrees C have been estimated as (1.63 +/- 0.29) x 10(-6)cm(2)/s and as (1.31 +/- 0.41) x 10(-6) cm(2)/s, respectively. Experiments show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 49 publications
(75 reference statements)
1
100
1
Order By: Relevance
“…The studies of tissue scattering kinetics under the penetration of immersion agents allowed the development of techniques for assessing the diffusion coefficients and permeability [35,43,47,[88][89][90][91][92][93][94]. Using these techniques, the diffusion rates of glucose and other medicinal preparations and immersion fluids were determined for the tissues of eye [91][92][93][94][95][96] [118][119][120][121][122]: dehydration of tissue components, partial replacement of interstitial fluid with the immersion agent, and structure modification or dissociation of collagen.…”
Section: Immersion Clearingmentioning
confidence: 99%
“…The studies of tissue scattering kinetics under the penetration of immersion agents allowed the development of techniques for assessing the diffusion coefficients and permeability [35,43,47,[88][89][90][91][92][93][94]. Using these techniques, the diffusion rates of glucose and other medicinal preparations and immersion fluids were determined for the tissues of eye [91][92][93][94][95][96] [118][119][120][121][122]: dehydration of tissue components, partial replacement of interstitial fluid with the immersion agent, and structure modification or dissociation of collagen.…”
Section: Immersion Clearingmentioning
confidence: 99%
“…Optical clearing of tissues induces tissue dehydration and refractive index matching by agent inclusion in the interstitial space of the tissue [3]. By placing an OCA in the interstitial space of the tissue and reducing the water content, the refractive index difference between the scatterers and the interstitial presented with results for the diffusion time for some OCAs such as dimethyl sulfoxide [17], glucose [18][19][20], mannitol [18], sucrose [21], glycerol [22], lactose and fructose [21] in different biological tissues and phantoms. A study that was recently published provided results for glucose diffusion permeability in normal and cancerous oesophageal tissues [23].…”
Section: Introductionmentioning
confidence: 99%
“…This method presents some advantages over others due to its capability to measure concentration in situ without interrupting the process as well as the simple post processing work thereafter. As such, the method has been used since in the early 1990s up until recently (Maier et al 1994, Chance et al 1995, Liu et al 1996, Tuchin et al 1997, Wang 2000, Vargas et al 2001, Yao et al 2002, Bashkatov et al 2003, Zhang et al 2013a,b, Trichet et al 2014, Ullah et al 2014, Pleitez et al 2015.…”
Section: Refractive Index Methodsmentioning
confidence: 99%
“…Numerous glucose diffusion studies have been reported for a vast number of applications ranging from TE (Hannoun and Stephanopoulos 1986, Weng et al 2005, Rong et al 2006, Papenburg et al 2007, Jin et al 2010, Podichetty et al 2014, diabetes management (Maier et al 1994, Wang and Musameh 2003, Boss et al 2012, modern laser medicine (Chance et al 1995, Liu et al 1996, Tuchin et al 1997, Wang 2000, Vargas et al 2001, Yao et al 2002, Bashkatov et al 2003, pharmaceutics (Andersson et al 1997), chemical engineering, filtration (Yaroshchuk et al 2011, Adams et al 2013), oil and fat industry (Miyagi et al 2012), and water desalination (Lonsdale et al 1965, Sherwood et al 1967. A review of these studies suggests that a number of different techniques could be applied to measure glucose concentration or diffusivity as discussed below.…”
Section: Measurements Of Glucose Concentration or Diffusivitymentioning
confidence: 99%